Harmony of Soul and Body dalam Pemikiran Aristoteles dan Relevansinya terhadap Identitas Manusia serta Kritik atas Masyarakat Konsumeris - Rasyidah, Hasna Safarina (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2026)
This study explores how the modern search for identity is often captured by a consumerist culture that promotes a fragmented self, overly dependent on materialism. The research aims to: (1) define Aristotle's concept of the harmony of soul and body; (2) analyze its contribution to understanding human identity; and (3) apply this concept to critique the patterns of consumerist society. This study uses a qualitative-philosophical method to analyze key texts, primarily Aristotle's De Anima, alongside a comparative-conceptual analysis contrasting Aristotelian thought with consumerist culture. The findings reveal that Aristotle’s hylomorphic framework posits the soul as the entelechy (functional actuality) of the body, creating an inseparable psycho-physical unity. Authentic human identity is therefore rooted in this integrated whole, with its ultimate purpose (telos) being a state of flourishing (eudaimonia). This is achieved through rational, virtuous activity (energeia) that forges a stable character (hexis) guided by practical wisdom (phronesis). In contrast, consumer culture is shown to be fundamentally pathological, as it disrupts this harmony by advocating for a superficial identity based on external ownership and image (pleonexia), leading to anxiety and profound dissatisfaction. In conclusion, Aristotle’s philosophy provides a robust critique of consumerism's fragmenting effect on the self and offers a timeless blueprint for building an authentic identity grounded in holistic well-being. It is recommended that future research apply this Aristotelian ethical framework to other contemporary challenges, including AI ethics, environmentalism, and educational reform.